LEADING DEEP LEARNING IN PRIMARY EDUCATION: HOW SCHOOL PRINCIPALS LEVERAGE TEACHER LEARNING COMMUNITIES TO ENHANCE EDUCATIONAL QUALITY - Nurasih, Beti; Rochmawati, Nur Intan (Universitas Islam Negeri Mataram, 2026)
This study explores how school principals lead the implementation of deep learning in primary education by leveraging teacher learning communities to enhance educational quality. Responding to increasing demands for meaningful, higher-order learning in the twenty-first century, the study adopts a qualitative case study design to examine leadership practices in a primary education context. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving school principals, teacher learning community coordinators, and primary school teachers. The findings reveal that leadership in deep learning is enacted through a coherent, integrated set of strategies. These include articulating and institutionalizing a shared pedagogical vision, positioning teacher learning communities as core mechanisms for collaborative professional learning, reorienting instructional supervision toward reflective dialogue, and managing structural and cultural conditions that sustain instructional change. Teacher learning communities function as mediating structures that translate leadership vision into classroom-level deep learning practices. When supported by reflective supervision and aligned organizational conditions, these communities foster teachers’ pedagogical innovation and collective responsibility for student learning. The study contributes to the literature on instructional leadership and professional learning communities by conceptualizing leadership for deep learning as a systemic and relational process. In practice, the findings offer insights for school leaders and policymakers seeking to embed deep learning into everyday professional routines in primary education